2007
DOI: 10.4152/pea.200702221
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Mild Steel in Sulphuric Acid Solution by Using Polyethylene Glycol Methyl Ether (PEGME)

Abstract: The corrosion inhibition of mild steel in one normal sulphuric acid solution by PEGME has been studied in relation to the concentration of the inhibitor as well as the temperature using electrochemical polarization (galvanostatic and potentiostatic) techniques. The results were supplemented with scanning electron microscopy and infra-red spectroscopy. All the methods employed are in reasonable agreement. There is no particular relationship of inhibition with concentration and temperatures. The thermodynamic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Corrosion inhibition of mild steel in sulphuric acid solution using polyethylene glycol methyl ether (PEGME) has been reported using electrochemical polarization (galvanostatic and potentiostatic) techniques [15]. It was found that PEGME is a very effective corrosion inhibitor for mild steel in acidic medium.…”
Section: +mentioning
confidence: 99%
“…Corrosion inhibition of mild steel in sulphuric acid solution using polyethylene glycol methyl ether (PEGME) has been reported using electrochemical polarization (galvanostatic and potentiostatic) techniques [15]. It was found that PEGME is a very effective corrosion inhibitor for mild steel in acidic medium.…”
Section: +mentioning
confidence: 99%
“…It has been acknowledged that mild steel is widely employed in most industries, due to its low cost and availability for the fabrication of various reaction vessels, such as cooling tower tanks and pipelines [1]. Mild steel corrodes as a result of an electrochemical reaction with its environment.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion inhibitor is one among them. Recently, plant extracts containing organic compounds having heteroatoms are evaluated for corrosion inhibition [1][2][3][4][5][6]. Azoles and N-methyl-p-aminophenol sulphate have been proved as excellent inhibitors of corrosion for mild steel in acid medium [7,8].…”
Section: Introductionmentioning
confidence: 99%